Carbon-Coated FeS as an Anode for Lithium Ion Batteries - Dong, Chenchu (Asian Journal of Chemistry, 2013)
Carbon sourced from thermal decomposition of sucrose is coated on FeS particles prepared by precipitating Fe2+ and S2- under atmospheric conditions. The effects of carbon content on the electrochemical performance of FeS anodes for use as lithium ion batteries are investigated. The cycling stability of the FeS anode is improved by the presence of a carbon coating. The FeS/C composite containing 10 wt. % carbon heat treated at 600 ºC shows the better performance than that of pristine FeS, with an initial capacity of 472.9 and 348.9 mAh/g after 20 charge/discharge cycles. The improved capacity stability of the carbon-coated FeS electrode is explained by the improvement of electronic conductivity.